+0  
 
0
112
1
avatar

6(x - 1) = 4(x - 2)

Guest Feb 14, 2017
 #1
avatar+87293 
0

6(x - 1) = 4(x - 2)      simplify

 

6x - 6  = 4x - 8     subtract 4x, add 6  from/to  each side

 

2x  = - 2     divide by 2

 

x  = -1

 

 

cool cool cool

CPhill  Feb 14, 2017

8 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.